Wirtualny nadawca w sieci. Wstępna kategoryzacja - Kaźmierczak, Marek (Wydawnictwo Naukowe UAM, 2005)
In the result of the emergence of the new media we are faced with unpredictable consequences for the textual communication. Contemporary metaphor of these "unpredictable consequences" is the World Wide Web (www). In this article - titled "Virtual Sender" - I am trying to describe the strong impact of the www exerted on the textual communication. The main issue of this article is the semiological status of the sender in the www. I am interpreting this category in three aspects: syntactic, semantic and pragmatic. Each of these aspects has a prevailing characteristic: for syntactic is an autopoietic function; for the semantic it is non-scaling function and for pragmatic aspect it is an autotheological function. Using these three aspects I am describing a very important relationship between the tools of communication and the subject of the communication. This article shows the main problem area connected with semiological status of the sender.
Virtual Sender on the Net. An initial Categorization